Sociodemographic Characteristics and Victimization at Police Officers - Capan, Mirko; Sindik, Joško (Kriminalističke teme, 2015)
Reason(s) for writing and research problem(s): The article deals with in Croatia rarely researched declared and covert victimization of the police officers, in relation to their selected sociodemographic characteristics. Aims of the paper (scientific and/or social): The aim of this study was to determine the relationship between variables of declared and hidden victimization of the police officers, with selected sociodemographic characteristics (number of children, size of city, length of service, level of qualifications and age). Other aim of the research was to determine gender differences in the variables related to the victimization of police officers. Methodology/Design: In correlational cross-sectional study, an intentional sample of respondents is examined, which included almost the entire population of parttime students: the police officers through five years of study in the academic year 2013/2014th on the Police College of the Ministry of Interior of the Republic of Croatia (N = 241). For the data collecting, a specially designed questionnaire is used. Research/paper limitations: Main limitations of this study are: positive non-random sample of participants and the questionnaire that can hardly cover all the relevant factors relating to the victimization of police officers. Results/Findings: The results showed that there are gender differences in the experience of victimization and lasting consequences of victimization. The frequency of both studied forms of victimization are related to the age, the size of the city and the education of police officers. General conclusion: Results and practice reflects the possibility of changing the awareness of police officers in the perception of their own victimization. Research/paper validity: The understanding of needs for the declaration of victimization can be a guideline for the professional creation of successful models of its prevention.